Does Guided Inquiry Affect Self-Regulated Learning? - Anam, Syahrul; Antika, Linda Tri (Lombok Institute, 2023)
Education currently requires students to manage their learning independently. This will support student achievement because students can set learning goals, monitor, set learning strategies, and even evaluate their learning. The application of the guided inquiry learning model is believed to be able to develop student self-regulated learning. This study aims to determine the effect of guided inquiry on student self-regulated learning. This research is a quasi-experimental study with a nonequivalent pretest–posttest control group design. The subjects of this study were 20 students in class X IPA A as an experimental class and class X IPA B with a total of 23 students as a control class. Self-regulated learning was measured using a questionnaire adapted from Marchis & Balogh. Prerequisite tests for normality, homogeneity, and prerequisite tests on the slope of the regression line between the covariates and the dependent variable are carried out before testing the hypothesis, followed by the Quade's Rank test. The study's results revealed that guided inquiry did not affect students' Self-regulated learning. Other factors or variables outside the research, such as learning motivation, learning regulation, discipline, self-confidence, and student learning styles, are thought to influence Self-regulated learning. In addition, the relatively short time of conducting guided inquiry is also believed to cause the lack of influence on student self-regulated learning.